Determinants of the onshore and offshore Chinese Government yield curves - Horst Loechel; Natalie Packham; Fabian Walisch (Frankfurt School of Finance & Management, 2013)
As part of its effort to internationalize the Renminbi, China's government has promoted the establishment of a regulated offshore Renminbi capital market hub in Hong Kong, where, among other activities, it issues RMB-denominated government bonds providing foreign investors access to Chinese bond markets. In a VAR model where yield curves are represented by Nelson-Siegel latent factors and which includes macroeconomic variables, we find that onshore government bond yields are primarily driven by policy-related factors such as the policy rate and money supply, whereas offshore government bond yields are additionally driven by market-related factors such as consumer confidence, GDP and FX rate expectations as well as liquidity constraints. At the current stage of market development there are virtually no spillover effects between the onshore and offshore government bond curves. Our results add quantitative evidence that China's efforts to internationalize its currency results in a simultaneous liberalization of its financial system.
Keywords: E43; E47; E63; G18; 330; Chinese government bond yields; Chinese offshore market; RMB; Hong Kong